Implementasi Binary Search Untuk Data Obat di Apotek - Ricky Yandy Darmawantoro; Yustina Retno Wahyu Utami; Kustanto Kustanto (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
The development of technology and information from day to day is always experiencing significant developments, with the technology aimed at facilitating and facilitating human activities in life. In this case the design of the application of the Binary Search Algorithm for the processing of Pharmacy Isna Farma data is made. The application program aims to facilitate the processing of drug data in pharmacies, so that the available supply can be controlled by the owner. In the search program using the keyword drug words or can with the drug code. The purpose of this research is to create a drug data search application system that is applied with a data search tool and change the system in the pharmacy from manual to computing. In research applying the Binary Search Algorithm, the Binary Search Algorithm is a technique with sorted data. In this thesis research using the Binary Search algorithm method with stages of analysis, system design, coding / construction, testing, and implementation. At the analysis stage, data collection is carried out, namely observation and literature study. At the system design stage using Unified Modeling Language (UML) including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. At the construction stage using the Java programming language Using the Netbeans application as a place for coding applications to become a system that is needed and the MySQL server as a database processor in the application. While the implementation of this system is an item data search application. The results of this study are a pharmacy Isna Farma, Drug data search by the Binary Search method with a total of 200 drug data, the average search time using the binary search method is 0.0030 second.The development of technology and information from day to day is always experiencing significant developments, with the technology aimed at facilitating and facilitating human activities in life. In this case the design of the application of the Binary Search Algorithm for the processing of Pharmacy Isna Farma data is made. The application program aims to facilitate the processing of drug data in pharmacies, so that the available supply can be controlled by the owner. In the search program using the keyword drug words or can with the drug code. The purpose of this research is to create a drug data search application system that is applied with a data search tool and change the system in the pharmacy from manual to computing. In research applying the Binary Search Algorithm, the Binary Search Algorithm is a technique with sorted data. In this thesis research using the Binary Search algorithm method with stages of analysis, system design, coding / construction, testing, and implementation. At the analysis stage, data collection is carried out, namely observation and literature study. At the system design stage using Unified Modeling Language (UML) including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. At the construction stage using the Java programming language Using the Netbeans application as a place for coding applications to become a system that is needed and the MySQL server as a database processor in the application. While the implementation of this system is an item data search application. The results of this study are a pharmacy Isna Farma, Drug data search by the Binary Search method with a total of 200 drug data, the average search time using the binary search method is 0.0030 second.